An Update on Molecular Biology of Cutaneous T Cell Lymphoma - Walia, Ritika; Yeung, Cecilia C. S. (Frontiers in Oncology, 2020)
Cutaneous T cell lymphomas represent a heterogeneous group of lymphoproliferative disorders defined by clonal proliferation of T cells present in the skin. The latest WHO classification in 2016 and WHO-EORTC classification in 2018 has updated the classification of these entities based on the molecular profile. Research in the field of molecular genetics of CTCL has allowed a better understanding of the biology of these tumors and has helped to identify potential targets for therapy that can be tailored to individual patients. In this review, we discuss the latest developments in the molecular profile of CTCLs including biomarkers for diagnosis, prognosis and potential therapeutic targets. We have also touched upon the utility of various molecular diagnostic modalities. For the purpose of this review, we researched papers in PubMed indexed journals in English literature published in the past twenty years using keywords CTCL, mycosis fungoides, molecular profile, molecular diagnosis, whole-genome profile, genomic landscape, TCR clonality.